KEEFEKTIFAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS PEMBELAJARAN TEMATIK SISWA KELAS IV - Dwi Sulistyani; Dwi Prasetiyawati; Asep Ardiyanto (Jurnal Guru Kita PGSD, 2018)
Abstract: Effectiveness of the Problem Based Learning Model on CriticalThinking Ability of Class IV Students Thematic Learning. This study aims toknow the effectiveness of problem-based learning model of the ability to thinkcritically thematic learning IV grade students. The method used in this research isquantitative research Pre-Experimental design with type one group pretest-posttestdesign. The subject of the research is IV grade students of SDN Sendangmulyo Blorawith a total of 20 students. Based on the results of the analysis show that learningusing problem-based learing model is effective to the critical thinking thematiclearning IV grade students, it is seen the average pretest which initially is 40 andafter doing the posttest the average value is 79. Learning with problem-based learingachieves maximum predefined criterion (KKM) that has been determined that is 65.Keyword : Problem Based Learning, Critical Thinking Ability, Thematic LearningAbstrak : Keefektifan Model Problem Based Learning terhadap KemampuanBerfikir Kritis Pembelajaran Tematik Siswa Kelas IV. Penelitian ini bertujuanuntuk mengetahui keefektifan model pembelajaran problem based learning terhadapkemampuan berfikir kritis pembelajaran tematik siswa kelas IV. Metode yangdigunakan dalam penelitian ini adalah penelitian kuantitatif Pre-Experimentaldesign dengan jenis one group pretest-posttest design. Subjek penelitian adalahsiswa kelas IV SD Negeri Sendangmulyo Blora dengan jumlah 20 siswa.Berdasarkan hasil analisis menunjukkan bahwa pembelajaran menggunakan modelproblem based learing efektif terhadap kemampuan berfikir kritis pembelajarantematik siswa kelas IV, dilihat rata-rata pretest yang awalnya adalah 40 dan setelahmelakukan posttest rata-rata nilainya adalah 79. Pembelajaran dengan problembased learing mencapai ketuntasan kriteria maksimal (KKM) yang telah ditentukanyaitu 65.Kata Kunci : Problem Based Learning, Kemampuan Berfikir Kritis, PembelajaranTematik